Da Nansen lanserte Nord i Tåkeheimen - Jølle, Harald Dag (Nordlit, 2012)
In 1911 Nansen published his major work In Northern Mists. Arctic Exploration in Early Times. The book deals with the exploration of the northern areas of the earth in earlier times, from antiquity before Pytheas to the Portuguese discoveries of the 16th Century. Working with the book, Nansen realized that many of the well-known and established sources could not be interpreted as literally as many of the historians ofhis time did. In the fall of 1910 he gave numerous lectures where he questioned the trustworthiness of the sagas as historical documents. Nansen faced considerable opposition which led to an extensive debate with among others Yngvar Nielsen and Finnur Jónsson. Later, Nansen's source criticism has proven to be far more in accordance with modern historical science than his opponents were.